Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.3036
|View full text |Cite
|
Sign up to set email alerts
|

SAT0225 Cereblon modulator CC-220 decreases naÏve and memory B cells and plasmacytoid dendritic cells in systemic lupus erythematosus (SLE) patients: exposure-response results from a phase 2A proof of concept study

Abstract: BackgroundCC-220 is a cereblon E3 ligase modulatory compound currently in development for the treatment of Systemic Lupus Erythematosus as well as other autoimmune conditions and multiple myeloma. As a high affinity ligand for cereblon, CC-220 administration results in significant reductions in ikaros (IKZF1) and aiolos (IKZF3), transcription factors which are genetically linked to SLE risk, and are overexpressed in the peripheral blood of SLE patients compared to healthy controls.ObjectivesTo describe the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recent observations indicate that IMiDs and PROTACs are poised to have a strong impact on drug discovery in years to come ( Table 1). The clinical efficacy of IMiDs is driven at least in part by their capacity to induce CRBN-mediated degradation of neo-substrates: cancer cells become resistant to the multiple myeloma IMiD drug lenalidomide upon mutation of a single amino acid in IKFZ3 that rescues this transcription factor from proteolytic degradation 7 ; haploinsufficient expression of CK1α sensitizes myelodysplastic syndrome (MDS) cells with deletion of chromosome 5q (del(5q)) to the CRBN-mediated degradation of CK1α by lenalidomide in patients with MDS (5q)15; and treatment with C-220, a CRBN modulator that induces a more potent degradation of IKFZ1 and IKFZ3 than previous IMiDs 16 , elicits positive response in patients with systemic lupus erythematosus in a phase 2a study 17 . Preclinical and clinical studies have demonstrated multiple routes of administration, including oral 18 .…”
Section: Progress and Lessons Learnedmentioning
confidence: 99%
“…Recent observations indicate that IMiDs and PROTACs are poised to have a strong impact on drug discovery in years to come ( Table 1). The clinical efficacy of IMiDs is driven at least in part by their capacity to induce CRBN-mediated degradation of neo-substrates: cancer cells become resistant to the multiple myeloma IMiD drug lenalidomide upon mutation of a single amino acid in IKFZ3 that rescues this transcription factor from proteolytic degradation 7 ; haploinsufficient expression of CK1α sensitizes myelodysplastic syndrome (MDS) cells with deletion of chromosome 5q (del(5q)) to the CRBN-mediated degradation of CK1α by lenalidomide in patients with MDS (5q)15; and treatment with C-220, a CRBN modulator that induces a more potent degradation of IKFZ1 and IKFZ3 than previous IMiDs 16 , elicits positive response in patients with systemic lupus erythematosus in a phase 2a study 17 . Preclinical and clinical studies have demonstrated multiple routes of administration, including oral 18 .…”
Section: Progress and Lessons Learnedmentioning
confidence: 99%
“…There were no signi cant outcomes in the disease activity indices, composite responder rates or adverse events in the following group of drugs; anti-dsDNA complexing Abetimus 30 selective JAK 1 and 2 inhibitors Baricitinib 31 , BTK inhibitors Evobrutinib 32 , Fenebrutinib 33 , high a nity cereblon ligand CC-220/Iberdomide 34,35 , tolerogenic peptides Edratide 36 , anti CD22 monoclonal antibody Epratuzumab [37][38][39] , anti IL-6 antibody PF-04326921 4040 Vobarilizumab 41 anti IL-10 monoclonal antibody BT063 42 , P140 peptide Lupuzor 43 and recombinant soluble human FcyRIIb SM101 44…”
Section: Group Of Drugs Without Signi Cant Resultsmentioning
confidence: 97%
“…CC-220 showed some efficacy but there were important safety issues in a 12-week, phase II, dose-escalation study of 42 patients and 14% of patients stopped treatment because of adverse effects. Higher doses of CC-220 were associated with neutropenia, pneumonia, and dermatitis ( 41 ).…”
Section: Intracellular Signalingmentioning
confidence: 99%